Creating a National Park, 1910 to 1926 - Carruthers, Jane (My University, 1989)
Popular histories of nature protection in southern Africa usually portray the prelude to the passing of the National Parks Act in 1926 as a contest between the forces of 'good' (those in favour of national parks) and 'evil' (those antagonistic or apathetic to the idea). In southern Africa the development of national parks has not been dispassionately evaluated and dedicated modern conservationists have constructed what might be described as an 'appropriate' history - indeed a proselytising one - ignoring considerations other than current conservation preoccupations. This romanticised view of past nature protection policies and attitudes is more akin to folklore than to history and it has distorted the paradoxical origins of protectionist endeavour. Such simplistic and inaccurate interpretations beg closer examination and a more objective and critical explanation is needed, one which takes cognisance, of the complexities of the South African political economy at the time. The creation of national parks - anywhere in the world - can only be understood in the context of the time and place in which this occurs.
African Studies Seminar series. Paper presented 15 May, 1989.
Keywords: National parks. South Africa; National parks